Randomized controlled trial of nebulized colistimethate sodium as adjunctive therapy of ventilator-associated pneumonia caused by gram-negative bacteria - Pinyo Rattanaumpawan (2018)
Background: Cases of ventilator-associated pneumonia (VAP) due to multidrug-resistant (MDR) Acinetobacter baumannii and Pseudomonas aeruginosa are common in hospitalized patients at Siriraj Hospital, Bangkok, Thailand. Parenteral colistimethate sodium (CMS) has been used for therapy of VAP caused by MDR A. baumannii and P. aeruginosa at Siriraj Hospital over the past few years, with modest favourable outcomes. Objectives: To determine whether nebulized CMS as adjunctive therapy of Gram-negative VAP was safe and beneficial. Methods: This was a randomized controlled study in 100 adults who developed Gram-negative VAP (clinical trial registration number: NCT00920270). All patients received systemic antibiotics according to the decisions of their responsible physicians. The patients were randomized to receive an additional 4 mL of nebulized sterile normal saline (NSS) (n=49) or nebulized CMS equivalent to 75 mg of colistin base in 4 mL of NSS (n=51) every 12 h until systemic antibiotic therapy of VAP was ended. Results: The baseline characteristics of the patients and conventional therapy of VAP in both groups were comparable. Most of the cases of VAP were caused by MDR A. baumannii and/or P. aeruginosa. All isolates of Gram-negative bacteria were susceptible to colistin. Favourable clinical outcome was 51.0% in the CMS group and 53.1% in the control group (P=0.84). Patients in the CMS group had significantly more favourable microbiological outcome when compared with patients in the control group (60.9% versus 38.2%, P=0.03). Bronchospasm was observed in 7.8% of patients in the CMS group and in 2.0% of patients in the control group (P=0.36). Renal impairment was observed in 25.5% of patients in the CMS group and in 22.4% of patients in the NSS group (P=0.82). Conclusions: Nebulized CMS as adjunctive therapy of Gram-negative VAP seems to be safe. However, a beneficial effect on clinical outcomes of adjunctive nebulized CMS for therapy of Gram-negative VAP was not ascertained. © The Author 2010. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.